Safety evaluation of matrine and its impact as a feed additive on the production performance of piglets - Cao, Zhigang; Wu, Yalin; Cong, Xiangming; Haseeb, Abdul; Sun, Panpan; Zhang, Hua; Fan, Kuohai; Yin, Wei; Yang, Huizhen; Zhang, Zhenbiao; Zhong, Jia; Wang, Jianzhong; et al. (Frontiers in Veterinary Science, 2025)
IntroductionPrevious studies have suggested that matrine may improve animal production performance, but its role and underlying mechanisms remain unclear.MethodsFollowing the determination of the LD50 of matrine in ICR mice, the long-term toxic effects of matrine on SD-weaned rats were evaluated. 0.375, 0.75, 1.5, and 3 mg/kg matrine were added to the feed of weaned piglets, respectively. The feed intake and body weight of piglets were recorded to evaluate the growth-promoting effect of matrine. The feces and blood of weaned piglets were collected to explore the mechanism of matrine improving the growth performance of piglets.ResultsOur findings imply that the LD50 of matrine in mice was 202.54 mg/kg, and matrine did not cause any hazardous effects when administered to rats within the range of 24.5–50 mg/kg for 180 days. Furthermore, supplementation of 0.375, 0.75, and 1.5 mg/kg matrine can increase ADG (average daily weight gain), and ADFI (average daily feed intake), and decrease the FCR (food conversion rate) of piglets. Additionally, 0.375 and 0.75 mg/kg matrine could increase the positive rate of porcine circovirus type 2 (PCV2) vaccine antibody in serum of piglets. We analyzed the correlation between intestinal flora, fecal metabolites, and growth performance through Mothur software and found that the impact of matrine on ADG, ADFI, and FCR might be associated to Gemmiger formicilis and thiamine.ConclusionThese findings revealed that matrine can improve the growth performance of weaned piglets by increasing the abundance of Gemmiger formicilis and thiamine content in feces.